Hubungan Motivasi Belajar terhadap Hasil Belajar Kognitif Siswa Kelas XI SMAN 3 Siak Hulu TA. 2022/2023 - Elyu Cahyani; Nurul Fauziah (Lembaga Pengembangan Kinerja Dosen, 2024)
This research aims to determine the relationship between motivation for studying biology in class XI SMA Negeri 3 Siak Hulu for the 2022/2023 academic year. This research is a type of descriptive research, the method used in this research is the correlational method. The sampling technique in this research used a saturated sampling technique. The results of data analysis, the correlation coefficient (rcount) is 0.43 with a significance level of 5%, which has a correlation in the low category. From hypothesis testing, it is obtained that tcount (4.83) > ttable (3.7). This means Ho is rejected and Ha is accepted. Then, from the results of the analysis of the coefficient of determination, the variable Learning Motivation (X) makes a positive contribution to the learning outcomes (Y) obtained by students by 18%, while 82% is determined by other variables or factors that influence student learning motivation which are not discussed in this research. The results of this research show that